Effect of credit constraint on yield: the case of ginger producers in southern and central Ethiopia - Tilore, Fetagn Gizachew; Shano, Berhanu Kuma; Shirko, Alula Tafesse; Hawitibo, Alemu Lambamo (Frontiers in Sustainable Food Systems, 2024)
This research investigated the impact of credit constraints on the yield of smallholder ginger farmers in southern and central Ethiopia. Employing a cross-sectional dataset from 343 randomly selected households, we utilized the endogenous switching regression model to address potential sample selection bias. In the first stage, the probit model identified livestock holding, marital status, farm size, distance to credit source, and information access as the primary determinants influencing the credit constraint status of smallholder ginger farmers. In the second stage, our analysis revealed that family size, farm size, and cooperative membership significantly affected ginger yield. Moreover, the average treatment effect suggests that the impact of credit constraints on ginger yield is significant, with credit-constrained farmers experiencing a greater positive effect compared to credit-unconstrained farmers. The findings underscore the intricate relationships between credit constraints, socioeconomic factors, and agricultural yield in the context of smallholder ginger farming.The implication of this research extends to informing policy decisions and intervention strategies aimed at alleviating credit constraints and enhancing the overall yield and livelihoods of smallholder ginger farmers in the studied regions. Based on the research findings, agricultural policies should prioritize interventions aimed at enhancing ginger yield. This may involve promoting cooperative membership and improving access to credit sources. Additionally, fostering livestock ownership and cooperative participation among credit constrained farmers can alleviate limitations and boost productivity, while policymakers should focus on reducing distance to credit sources and enhancing access to information for effective mitigation of credit constraints.